RANCANG BANGUN APLIKASI MANAJEMEN PESANTREN DIGITAL UNTUK EFISIENSI SDM DAN KEUANGAN DI PESANTREN UMMUL QURO - prabowo, budhi; mulyadi, mulyadi; Ridwan Maulana, San (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
Human resource (HR) and financial management in Islamic boarding schools in Indonesia still face various structural challenges, especially related to the limitations of digital-based information systems. This Community Service Research (PKM) aims to design and build an integrated digital pesantren management application to improve the efficiency of human resource and financial management at the Ummul Quro Islamic Boarding School, Pondok Cabe Ilir, Pamulang, South Tangerang City. The method used is qualitative descriptive with a participatory action research (PAR) approach, involving pesantren administrators, educators, and students actively in the system design process. The results of the activity show that the digital application developed is able to integrate attendance management, payroll, financial reports, and student administration in one integrated platform. The implementation of this application contributes significantly to improving operational efficiency and transparency in the management of Islamic boarding schools. This finding has strategic implications for the development of digitalization of Islamic boarding schools nationally in the face of the era of globalization.